PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Students' Journal of Accounting and Banking, 2013)
The objective of this study is to examine the influence of company size, company profile, profitability, size of the board of commissioners, leverage, managerial ownership and operation efficiency ratio on the disclosure of corporate social pesponsibility on the LQ-45 company listed on the Indonesia Stock Exchange (IDX) during the period 2009 to 2011. The Population in this study are all companies listed on the Indonesia Stock Exchange (IDX) during the period 2009 to 2011. The samples were selected using purposive sampling method is LQ-45 company amount 17 companies. Technique test of data is by using multiple linear regression analysis.The result showed that the variables have a significant negatively influence on the disclosure of corporate social responsibility is the size of the board of commissioners and managerial ownership. While company size, profitability, company profile, leverage, and operating efficiency ratio does not significantly influence the disclosure of corporate social responsibility.Keywords: company characteristics and corporate social responsibility.